Pengadaan Bahan Pustaka Dinas Perpustakaan Dan Arsip Daerah Kabupaten Muaro Jambi - Irpina, Wiwin (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
ABSTRACT This study aims to determine the process of procurement of library materials at the Regional Library and Archives Service of Muaro Jambi Regency. The research method used is library research methodologically classified as qualitative research with a descriptive approach in the form of a case study which aims to explain the procurement of library materials at the Regional Library and Archives Service of Muaro Jambi Regency. Data collection techniques used were through observation and interviews. The findings of the study are (1) the Regional Library and Archives Office of Muaro Jambi Regency has carried out library material procurement activities through purchases from book agents, bookstores, gifts, entrances and through assistance once a year. (2) The Regional Library and Archives Office of Muaro Jambi Regency has never procured serial publications, as well as non-book materials (recorded works) because according to them library materials are rarely needed by users. (3) The procurement of library funds for library materials is not running properly as seen from the constraints that occur, namely the lack of spending funds for the procurement of library materials both from series published library materials and recorded library materials, as well as the lack of attention from leaders leading to the procurement of library materials so that the available collections incomplete, not up to date and not used by the user. From these findings, it is hoped that the Regional Library and Archives Office of Muaro Jambi Regency will continue to procure collections of serial publications and recorded works because these collections can increase the number of collections available, create public interest in reading and add to the repertoire of library collections. Furthermore, the Regional Library and Archives Service of Muaro Jambi Regency should process funds properly by paying attention to user needs so that library materials purchased are in accordance with user education. Then also the head of the library must pay more attention that leads to the procurement of library materials so that the available collections can be more up to date, complete, and can be used by users. Keywords: Library Material Procurement, Library Collection, Public Library